Hibridismo y variedad en una novela corta de Joseph Penso de la Vega y Miguel de Barrios: Finezas de la amistad y triunfo de la inocencia (¿Ámsterdam?, 1683) - Fernando Copello (Mélanges de la Casa de Velázquez, 2013)
Two writers resident in Amsterdam in the 17th century (Joseph Penso de la Vega and Miguel de Barrios) penned a short novel, Fineza de la amistad y triunfo de la inocencia, an extremely interesting example of mixed genres where the narrative hints at enigmas, contains letters and poems, presents a catalogue of games, etc.—in other words variety is one of its most striking features. At the same time, the paratext evokes Hispano-Jewish intellectual dialogue in Amsterdam. The aim of the two authors was to create an Italianesque novel as if written in Spain, printed in Amsterdam, and with an Antwerp typeface. This short novel is an example of mixing or cooperation of authors, mixing of subjects, forms and genres, and deliberate paratextual hybridism.